Tratamento endodôntico de dentes permanentes imaturos: Avaliações in vitro e computacionais de diferentes parâmetros de interesse - Souza, Gabriela Leite de (2023)
This study aimed to evaluate in vitro and through computational tests several procedures and materials used in pulpal and regenerative therapies in immature teeth. In chapter 1, bioactive glass SiO2–Na2O–CaO–P2O5 (SNCP) and SNCP doped with 10% titanium (SNCP:10Ti) were synthesized, characterized and evaluated in solution for viability, migration and expression of alkaline phosphatase (ALP) in human dental pulp cells. In chapter 2, zinc oxide nanocrystals doped with 1% calcium (ZnO:1.0Ca) were manipulated with propylene glycol (PRG) or polyethylene glycol with propylene glycol (PEG+PRG) and were investigated for cytotoxicity, radiopacity, pH and penetration into dentinal tubules compared with calcium hydroxide pastes (Ca(OH)2). In Chapter 3, immature permanent teeth with simulated replacement root resorption were filled with Biodentine (BD), BioC Repair (BCR), and through apexification with mineral trioxide aggregate (MTA) and were tested for fracture toughness. Additionally, the effects of these materials on in vitro induced osteoclastogenesis were evaluated. In Chapter 4, the stress distribution of revascularized teeth with different root development (RET) and of immature permanent teeth treated with apexification with MTA and reinforced with intraradicular composite resin (RC) was evaluated during bite loading using method of analysis twodimensional finite elements. Finally, in chapter 5, the multidisciplinary treatment of a 9 yearold girl who suffered a complicated fracture of the crown in the upper left central incisor and a late necrosis in the upper left lateral incisor, which were respectively treated through partial pulpotomy followed by endodontic treatment radical and regenerative endodontic procedure, has been reported. The SNCP and SNCP:10Ti bioactive glasses were correctly synthesized. Cytotoxicity levels were high at the 1:1 dilution (p<0.05) and similar to the control at 1:8 and 1:16 (p>0.05). However, SNCP:10Ti was less cytotoxic at the 1:8 dilution (p<0.05). The groups showed similar ALP migration and expression (p>0.05). ZnO:1.0Ca pastes showed lower viability in 1:1 and 1:2 compared to Ca(OH)2 (p<0.0001). Ca(OH)2 pastes showed higher pH values and lower radiopacity than ZnO:1.0Ca (p<0.05). ZnO:1.0Ca pastes had greater penetration depth than Ca(OH)2 in the apical third (p<0.0001). No significant difference in fracture toughness was observed between teeth filled with BCR, BD or MTA apexification (p>0.05). BD inhibited osteoclastogenesis similarly to BCR and MTA (p>0.05), however BCR showed a lower percentage of osteoclasts compared to MTA (p<0.0001). Increasing root dentin thickness after RET had no significant benefit in the stress distribution of immature permanent teeth. RC showed less accumulation of intraradical stresses in the cervical region compared to the RET models. In the presented clinical case, the 4year followup of the patient confirms evidence of clinical success of the proposed treatment, since the patient was asymptomatic, and all teeth involved demonstrated complete root formation and periapical normal appearance.